A RETROSPECTIVE ANALYSIS OF SPONTANEOUSLY REPORTED ADVERSE DRUG REACTIONS TO ANTIRETROVIRAL THERAPY DURING AND POST-TRANSITIONAL PHASE OF DOLUTEGRAVIR - SWAROOPA, KATIKITALLA; DURGA DEVI, PILLA S SURYA; KEERTHANA, S; SRINIVASA RAO, R (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The main objective of this study was to analyze the pattern of reported adverse drug reaction (ADRs) in people receiving antiretroviral therapy (ART) mainly during and post-transitional phase of dolutegravir-based regimens. Methods: This is a retrospective observational study initiated after the approval of the Institutional Ethics Committee and from the ART Center. Sources of data are spontaneously reported ADR data of human immunodeficiency virus (HIV) persons to the ADR monitoring center (AMC). Results: A total of 190 patients who are on ART reported at AMC from April 2020 to June 2022 had a total of 204 ADRs. Among them, 108 (57%) were females and had a higher prevalence than 82 (43%) males. ADRs were higher among the age group of 41–50 years (33.68%) followed by 31–40 years (32.10%). Among dolutegravir-based regimens, tenofovir, lamivudine, and dolutegravir were given to more patients (118). The most common ADRs encountered were peripheral neuropathy 16.66%, followed by hyperglycemia (14.21%), renal toxicity (10.29%), hyperbilirubinemia (9.31%), and anemia (7.84%) of all ADRs. Conclusion: In this study, it has been observed that HIV patients on dolutegravir-based regimens are associated with more ADRs. Nervous system disorders were the most commonly observed group of ADRs, followed by metabolism and nutritional disorders, the others being skin diseases and renal toxicity. This incidence of ADRs to ART calls for efficient pharmacovigilance surveillance to improve patient care and drug safety.